2006
DOI: 10.1111/j.1439-0531.2006.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Findings and Hormonal Profiles in the Postpartum Balady Goats

Abstract: Twenty-six Balady goats categorized according to parity into primiparous and pluriparous goats were used to investigate bacterial flora of the genital tract and hormonal profiles during the postpartum (PP) period. Escherichia coli and Staphylococcus aureus were isolated in pure or mixed culture from the uterus. Arcanobacterium pyogenes was isolated from swabs obtained from the vagina and cervix of one primiparous goat. Uteri and cervices but not vaginas were free of bacterial contamination by day 10 PP except … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…For the PRL assay, anti-ovine PRL, NIDDK-anti-oPRL (AFP-C3581069II), and ovine purified PRL, NIDDK-oPRL-I-2 (AFP-7150B), were used for iodination and reference standards. The inter-assay coefficients of variation (CVs) for estradiol, progesterone, FSH, LH, immunoreactive-inhibin and PRL were 3 …”
Section: Hormonal Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…For the PRL assay, anti-ovine PRL, NIDDK-anti-oPRL (AFP-C3581069II), and ovine purified PRL, NIDDK-oPRL-I-2 (AFP-7150B), were used for iodination and reference standards. The inter-assay coefficients of variation (CVs) for estradiol, progesterone, FSH, LH, immunoreactive-inhibin and PRL were 3 …”
Section: Hormonal Analysismentioning
confidence: 99%
“…Follicular activity resumed as early as Day 13 in the ovaries of postpartum goats, and medium-or large-sized follicles were present in the ovaries soon after [3]. Sosa [4] showed that the goat ovarian cyclicity resumed after complete uterine involution at the 5th week postpartum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the type of bacteria present and the role they play is not well understood, under stressful conditions they may cause disease (1). A variety of bacteria have been isolated from the genitalia of the doe and these include (Staphylococci, streptococci , Actinomyces, Pseudomonas, E.coli, mycoplasma and Brucella species (2). , these organisms have been associated with disease condition of the genitalia of animals (3).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly in the ewe, the uterus is rendered resistant to bacterial infection when progesterone levels are low, while the uterus becomes susceptible to post partum infections with progesterone supplementation [5]. In goats, low estrogen levels with low progesterone probably enhanced the uterine immune system post partum [6]. Thus resistance to uterine infections have been reported among livestock when concentrations of progesterone are basal, yet when concentrations of progesterone are increased animals become more susceptible to infection [4,[7][8][9].…”
mentioning
confidence: 99%